Identificación de especies de diatomeas epilíticas asociadas a diferentes niveles de calidad del Agua del Río Cutuchi en la provincia de Cotopaxi, periodo marzo - mayo 2018. - Acosta Granda, Víctor Daniel (2018)
In this research, it was possible to identify a total of 60 species of epilithic diatoms associated with different levels of water quality from the Cutuchi River in Cotopaxi Province; a sampling was done in each of the points recognizing thus, those of greater influence; at point one or also known as a clean point, the presence of 8 microalgae was found: Achnanthidium minutissimum, Gomphonema sp, Gomphonema lagenula, Mayamaea permitis, Nitzschia acidoclinata, Navicula cryptotenella, Planothidium lanceolatum, Planothidium frequentissimum; while at point two or midpoint of contamination, 9 microalgae were located: Gomphonema parvulum, Gomphonema pumilum var. rigidum, Mayamaea permitis, Navicula cryptotenella, Navicula lanceolata, Navicula, gregaria, Navicula tripunctata, Nitzschia inconspicua, Nitzschia amphibia; and finally at the point three or called dirty spot, among the most abundant are: Navicula nota, Navicula gregaria, Navicula lanceolata, Navicula cryptotenella, Nitzchia palea, Nitzschia inconspicua, Pinnularia sp. To calculate the rate of water quality in the months of March, April and May, 9 parameters between physico-chemical and microbiological were processed through the IQAData program, and they projected an appropriate scale, where at point 1 it was obtained a rating of Good with an average of 81.60, while for points 2 and 3 the rating was Bad, with values of 44.12 and 33.56 respectively. Subsequently, the theoretical ITCA and tables were compared; for point 1, the theoretical ITCA had a value of 1.37, which correlated with the ITCA of tables is in the range of 1.0 to 1.5 which shows an Oligotrophic contamination level; in point 2 the theoretical ITCA has a value of 2.32 and compared with the table ITCA falls within the range 1.5-2.5 with a degree of contamination β-mesotrophic and, for point 3 was obtained a Theoretical ITCA of 2.84 compared with the ITCA of tables resulted in a level of α-mesotrophic contamination since it was found in a range of 2.5 to 3.5.